EFFECTIVENESS OF LOW GLYCEMIC INDEX HIGH PROTEIN DIET ON AGES AND INTERLEUIKIN-6 LEVELS IN PCOS-INSULIN RESISTANCE MODEL MICE: Effectiveness of Low Glycemic Index High Protein Diet on Ages and Interleuikin-6 Levels in PCOS Insulin Resistance Model Mice - Hany Puspita Aryani; Elizazihni Zatihulwani; Sugiyanta (Masters Program in Public Health, 2025)
Background: A dietary approach that is low in carbohydrates and high in protein may enhance the management of polycystic ovary syndrome (PCOS) by assessing serum concentrations of Interleukin 6 and AGEs. This study aimed to evaluate the effects of a low carbohydrate, high protein diet in PCOS insulin resistance model mice on the level of AGEs and Interleukin 6. Subjects and Method: This study used a post test only control group design, true experimental design. The number of samples in this study was 18 mice divided into 3 groups. The number of samples in each group was added 20% of the initial number of samples as a reserve for mice that died. The sample comparised six female rattus norvegicus mice aged 2-3 months, weighing 150-200 gr. The independent variable was the low glycemic index high protein (LGHIP) diet. The dependent variables were AGEs and Interleukin-6. Examination of blood serum of mice ELISA measurement of AGEs and IL-6 levels. Anova and Post Hoc tests were performed to compare AGEs and IL-6 levels between groups. Results: LGIHP diet decreased IL-6 levels of PCOS-IR model mice (p= 0.002). There was a significant difference between the K- and P groups in IL-6 levels (p= 0.002). Changes in AGEs levels between groups showed a significant difference (p= 0.015). Post Hoc test for AGEs levels showed significant differences between the K- and P groups (p= 0.023), the K+ group with the P group (p= 0.047). Conclusion: The LGIHP diet may serve as a potential dietary strategy for managing PCOS-IR. Regulating diet especially carbohydrates and glucose can improve the response to glucose secretion and inflammatory pathways, thereby affecting the significant risk of PCOS severity. Keywords: low glycemic index high protein diet, AGEs, IL-6, polycystic ovary syndrome.